New Copper(I) Complex with a Coumarin as Ligand with Antibacterial Activity Against Flavobacterium Psychrophilum - Guerrero-Nunez, J; Guerrero-Nunez, J; Modak-Canobra, B; Tello-Reyes, M; Arce-Ortega, P; Arce-Ortega, P; Aldabaldetrecu-Urbieta, M; Aldabaldetrecu-Urbieta, M; Parra-Mardonez, N (Multidisciplinary Digital Publishing Institute (MDPI), 2020)
A new copper (I) complex, [Cu(NN1)2](ClO4), was synthesized, where NN1 was a imine ligand 6-((quinolin-2-ylmethylene)amino)-2H-chromen-2-one obtained by a derivatization of natural compound coumarin. The structural characterization in solution was done by NMR techniques, UV-Vis and cyclic voltammetry. The potential antibacterial effect of [Cu(NN1)2](ClO4), was assessed for F. psychrophilum isolated 10094. F. psychrophilum is a Gram-negative bacterium which causes diseases such as bacterial cold-water disease and rainbow trout fry syndrome, causing large economic losses in the freshwater salmonid aquaculture industry. This complex show to have antibacterial activity against F. psychrophilum 10094 at non-cytotoxic concentration in cell line derived from trout (F. psychrophilum 10094 IC50 16.0 ± 0.9; RT-GUT IC50 53.0 ± 3.1 μg/mL). © 2020 by the authors.